Analisis Persepsi Karyawan Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan CV. Kurnia Meubel Kota Sukabumi - Eneng Susan; Faizal Mulia Z; Asep Muhamad Ramdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe employee perceptions, work environment and job satisfaction. Then to analyze employee perceptions, work environment and employee job satisfaction on CV. Kurnia Furniture Sukabumi City. The reason the researcher conducted this research was because there were problems with employee job satisfaction. The object of this research is employee perception, work environment and employee job satisfaction. The research method used in this research is descriptive and associative using a quantitative approach. The population in this study are all 53 employees using saturated sampling. The type of data used is primary and secondary data, the measurement of this study uses a Semantic Differential scale. The data analysis techniques in this study are validity and reliability tests, multiple linear regression including correlation coefficients, determination and research model testing (F test) and research hypothesis testing (T test). The results of this study indicate that the variable of employee perception and work environment on employee job satisfaction has a value of 0.822 which is included in the criteria for a very strong relationship. The relationship between employee perception variables and employee job satisfaction is 0.676. And the magnitude of the influence of employee perceptions and work environment on employee job satisfaction is 67.6% and 32.4% is influenced by other factors not included in this study. Keyword: Employee Perception, Work Environment, Job Satisfaction